Analisis Tingkat Pengetahuan Mahasiswi Mengenai Konsep Taharah Dalam Konteks Istihadah - Muhammad Jamaluddin Al Hamza; Nurhaliza Nuhaliza; Zahra Fibriyani; Wanda A Aliah Zahro (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2024)
Islam is a religion that upholds the concept of purity. Purification or also called taharah has a broad meaning not only limited to ablution, taharah is to purify oneself, clothes, and places of worship from hadas and najis according to Islamic law. This study aims to determine whether Muslim women know about istihadah, the kinds of blood istihadah in Islamic law and its implications in worship. This study uses a descriptive quantitative research type with a survey approach to analyze female students' level of knowledge regarding the concept of taharah in cases of istihadah. Data collection techniques are carried out through questionnaires. The collected data is then analyzed using descriptive statistics, such as frequency and percentage.. The results showed that female students' understanding of the concept of taharah, especially istihadah, was at a sufficient level, not too low but also not optimal. It is hoped that with this research, more women will realize the importance of delving further into the concept of taharah, especially istihadah.